Physicochemical Characteristics Of Temulawak (Curcuma xanthorrhiza Roxb.) Instant Powder By Crystallization Method - Dian Purbasari; Alfina Sabrin Eka Febrianti; Sutarsi Sutarsi; Ning Puji Lestari; Iwan Taruna (Universitas Muhammadiyah Mataram, 2024)
Temulawak is a medicinal plant whose rhizome is utilised. To extend the shelf life, temulawak is processed into instant powder drink through crystallisation method with the help of sugar as sweetener and crystallisation agent. This study aims to analyse the physicochemical characteristics of temulawak instant powder produced from the crystallisation method and determine the best sugar concentration on the characteristics of the instant powder produced. This study used a completely randomised design (CRD) method with one factorial, namely different sugar concentrations (40%, 50%, and 60%). The results showed that different sugar concentrations affected the parameters of water content, degree of fineness (FM), grain average (D), redness level (a), yellowish level (b), water absorption and yield. Moisture content values ranged from 2.14 - 2.72%; FM values ranged from 1.39 - 2.05; D values ranged from 0.011 - 0.017 mm; brightness values ranged from 74.49 - 77.43; redness values ranged from 29.52 - 31.16; yellowness values ranged from 67.56 - 69.92; bulk density values ranged from 0.478 - 0.495 g/cm³; water absorption values ranged from 7.74 - 9.01% and yield values ranged from 36.07 - 50.99%. The best formulation of different sugar concentrations is the treatment formulation with 40% sugar concentration.